Theobromine inhibits differentiation of 3T3-L1 cells during the early stage of adipogenesis via AMPK and MAPK signaling pathways. Issue 7 (8th July 2015) - Jang, Yeon Jeong; Koo, Hyun Jung; Sohn, Eun-Hwa; Kang, Se Chan; Rhee, Dong-Kwon; Pyo, Suhkneung
<x xml:space="preserve">Abstract</x> Theobromine decreased the accumulation of lipid droplets in a concentration-dependent manner.